THE PARENTS’ ROLE IN MAINTAINING GAYONESE LANGUAGE BY INTERMARRIAGE FAMILIES IN LANGSA - Merina Devira Devira; Chairuddin Chairuddin; Zulkifli Zulkifli (Program Studi Pendidikan Sejarah - Universitas Samudra, 2018)
The research problem of this research is divided into two: (1) how Gayonese language is maintained in intermarriage families in Langsa and (2) how the parents' roles are in maintaining Gayonese language in intermarriage families in Langsa. This study uses a qualitative descriptive method and the instrument of this research is observation and interview. Steps of collecting data include observing the location of the research, getting participants and then doing interviews with participants, which are four families. The family is intermarriage family that is marriage from one tribe to another tribe. In this research, Gayonese intermarriage families are as the subject of research. The results of the analysis show that there are four Gayonese intermarriage families in Gampong Serambi Indah that can inherit their Gayonese language to their children. Furthermore, based on factor and domain analysis affecting their language to be maintained is the role of parents to teach them Gayonese language. Then there are three domains also that influence gayonese language to be maintained to the second generation: environment, home, and school.